Direct Organocatalytic Asymmetric para C–H Aminoalkylation of Aniline Derivatives Affording Diarylmethylamines - Wang, Cheng-Long; Li, Yong-Ling; Wang, Le; Wang, Xun-Hui; Zhou, Jia; Bai, He-Yuan; Ding, Tong-Mei; Sun, Zhen-Liang (Synthesis, 2023)
An efficient method to directly catalyze asymmetric para C–H aminoalkylation of aniline derivatives to prepare chiral diarylmethylamine system was developed. Aniline derivatives underwent an enantioselective aminoalkylation in the presence of chiral phosphoric acid, affording a series of optically active diarylmethylamine products in good yields and enantioselectivities (73% yield, 91% ee). Furthermore, this method could be used to prepare the key intermediate of chiral drug levocetirizine.
Keywords: organic catalysis; aniline derivative; aminoalkylation; diarylmethylamine; asymmetric synthesis